Jurnal ANALISA SIFAT FISIS AGREGAT LIMBAH BAHAN BAKAR BATU BARA DAN PEMANFAATANNYA UNTUK BAHAN BANGUNAN NON STRUKTUR - Satriyo Utomo; Indah Rosanti; Akhmad Muhtadi; Hartanto Wahyu Sasongko (Politeknik Negeri Jakarta, 2022)
Physicality tests conducted in this study are: filter analysis test, water content test, mud level test, type weight test and absorption and organic level test. For testing of non-structural building materials in the form of Bricks and Paving Blocks. The manufacture of brick test objects and paving blocks uses two aggregates, namely from coal fuel waste and from natural sand. The results of physicality testing illustrate that coal fuel waste aggregates have lighter content weight, coarse grain and have a large absorption than natural sand. Testing of sludge levels and the organic content of natural sand and coal waste aggregates both did not meet quality standards for fine aggregates. The results of the quality testing of paving blocks and bricks get a rebound reading that is close to the same. For dry weight and ssd weight paving blocks and bricks from coal fuel waste is lighter than natural sand.